COMPARATIVE EVALUATION OF TITANIUM AND BIORESORBABLE FIXATION IN LEFORT I OSTEOTOMY: A RANDOMIZED CLINICAL STUDY - Mannobjonova Mukhina Abdullojon Qizi; Sokhibov O.M (TADQIQOTLAR, 2025)
ANNOTATION LeFort I osteotomy is a widely used surgical procedure for correcting maxillary deformities. Stable fixation is essential for maintaining postoperative skeletal positioning. Titanium plates provide excellent mechanical strength but remain permanently in the facial tissues and often require removal. Bioresorbable plates were developed to avoid long-term hardware retention, although concerns remain regarding their initial stability. This study compares titanium and bioresorbable fixation systems in patients undergoing LeFort I osteotomy. Clinical and radiographic evaluations were conducted to assess skeletal stability, postoperative comfort, and complications. The findings show that titanium fixation offers superior early stability, while bioresorbable fixation improves patient comfort and eliminates the need for secondary removal. Long-term skeletal stability was comparable in both groups, indicating that both systems are effective and should be chosen based on patient needs and surgeon preference.